Feasibility of advanced development of resource universities in the CIS - A. E. Vorobiov; G. K. Tashkulova (Горные науки и технологии, 2016)
The main concept on which the philosophy of a traditional university is based is as follows: state finances their work, and the people use the results obtained. The ways of gradual transition of traditional universities into modern institutions, including international and network ones, are shown. It is demonstrated that current stage of globalization actually means decline of the German model of traditional university functioning. The challenges that are specific to resource universities are considered. It was revealed that addressing the challenges should be based on forming the ideology of sustainable development of human society. The strategy of priority development of resource universities is presented.